Representations of Generation Z’s Religiosity in Hanan Attaki’s Da’wah Content: A Study of the Psychology of Religion by Zakiah Daradjat - Septya Nyngrum, Agnysh; Lubis, Dahlia (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the dialectical relationship between religion and digital media, focusing on the role of Muslim influencers in increasing the religiosity of the younger generation. In the era of information disruption, social media is often a source of digital anxiety and spiritual emptiness. However, the emergence of Muslim influencers has transformed digital platforms into a new space for the transmission of more inclusive religious values. Using a descriptive qualitative method grounded in Zakiah Daradjat’s perspective on the Psychology of Religion, this study examines how digital spiritual content affects the psychological state of the audience. The results show that Muslim influencers have successfully packaged Islamic teachings into an effective “virtual spiritual therapy” tool through personal and aesthetic narratives. The increase in religiosity observed in this study is not merely cognitive but manifests in real-world practices, including enhancing the quality of worship as a psychological need, internalizing patience (sabar) and trust in God (tawakal), and finding the courage to engage in meaning reconstruction to let go of the past. The conclusion confirms that the synergy between religion and media, when managed by the appropriate authorities, can restore mental health, provide inner peace, and serve as a spiritual fortress for the younger generation as they navigate the complexities of modern life.